(untitled) (Research, Society and Development, 2021)
The aim of the present study is to perform a literature review on the correction of gingival smile, to discuss the role of periodontal aspects related in this process, as well as to define which technique is considered, of first choice in the correction of gingival smile. An electronic search of publications was carried out in the PubMed, Lilacs and Scielo databases, using the following keywords, obtained according to the Medical Subject Headings (MeSH): Gingivectomy, Gingival hyperplasia, Gingivoplasty, with the Boolean operator “OR”. As a result, all techniques for correcting gingival smile have effectiveness, some in isolation, and others associated with other techniques, as is the case with conventional surgery, associated with the use of botulinum toxin. It is concluded that the surgical technique with osteotomy, associated with the use of botulinum toxin, presented better results, as it provides greater comfort to the patient during and after the procedure, has a low recurrence rate and has an excellent prognosis for the patient.